2019
DOI: 10.1016/j.matchemphys.2019.121852
|View full text |Cite
|
Sign up to set email alerts
|

A facilitated synthesis of hierarchically porous Cu–Ce–Zr catalyst using bacterial cellulose for VOCs oxidation

Abstract: Highly active CuO-CeO 2-ZrO 2 catalysts were prepared by sol-gel method, using environmentally friendly bacterial cellulose (BC) as structure directing regent. The catalyst designed with commercial BC (Com-BC) exhibited catalytic performances in toluene (T 100 =220 o C) and ethyl acetate oxidation (T 100 =170 o C) superior to the catalysts prepared by traditional methods. Furthermore, excellent stability was obtained and no deactivation was observed during the 100 h on stream in toluene and ethyl acetate oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…For CO oxidation, the r cat (2.04 × 10 −6 mol CO /(g cat s)) at 70 • C over 15Cu/OMS-2 was much higher than that (3.1 × 10 −7 mol CO /(g cat s)) at 100 • C over Pd/CuMnO x [28]. For ethyl acetate oxidation, the r cat (9.82 × 10 −7 mol ethyl acetate /(g cat s)) over OMS-2 at 180 • C and those (1.25 × 10 −6 -1.74 × 10 −6 mol ethyl acetate /(g cat s)) over xCu/OMS-2 at 180 • C were higher than that (2.30 × 10 −7 mol ethyl acetate /(g cat s)) over Cu-Ce-Zr prepared by Dou et al [29]. For toluene oxidation, the r cat (9.82 × 10 −7 mol toluene /(g cat s)) over OMS-2 at 260 • C and those (1.31 × 10 −6 -1.85 × 10 −6 mol toluene /(g cat s)) over xCu/OMS-2 at 260 • C were higher than that (4.09 × 10 −7 mol toluene / (g cat s)) over OM-CuMn0.25 prepared by Aguilera et al [26].…”
Section: Catalytic Performancementioning
confidence: 70%
“…For CO oxidation, the r cat (2.04 × 10 −6 mol CO /(g cat s)) at 70 • C over 15Cu/OMS-2 was much higher than that (3.1 × 10 −7 mol CO /(g cat s)) at 100 • C over Pd/CuMnO x [28]. For ethyl acetate oxidation, the r cat (9.82 × 10 −7 mol ethyl acetate /(g cat s)) over OMS-2 at 180 • C and those (1.25 × 10 −6 -1.74 × 10 −6 mol ethyl acetate /(g cat s)) over xCu/OMS-2 at 180 • C were higher than that (2.30 × 10 −7 mol ethyl acetate /(g cat s)) over Cu-Ce-Zr prepared by Dou et al [29]. For toluene oxidation, the r cat (9.82 × 10 −7 mol toluene /(g cat s)) over OMS-2 at 260 • C and those (1.31 × 10 −6 -1.85 × 10 −6 mol toluene /(g cat s)) over xCu/OMS-2 at 260 • C were higher than that (4.09 × 10 −7 mol toluene / (g cat s)) over OM-CuMn0.25 prepared by Aguilera et al [26].…”
Section: Catalytic Performancementioning
confidence: 70%
“…[34] The lower Cu + ions content on the surface of Pt 0.01 Cu 0.4 Ce 0.3 Zr 0.3 O x samples was mainly due to the large amount of bulk CuO generation. [35] The O1s spectrum shown in Figure 8c can be fitted to two main peaks. The peaks at the binding energy of the 529.6-529.9 eV region correspond to the oxygen in the catalyst lattice (O L ), and the other binding energy centered in the 531.0-531.5 eV region is assigned to the surface chemically adsorbed oxygen (O A ).…”
Section: Xps Spectramentioning
confidence: 99%
“…The supported transition metal-based catalysts have been shown to have higher catalytic activity compared to unsupported catalysts (Li et al 2016). To increase the catalytic activity of transition metal-based catalysts, two (Georgescu and Bombos 2016;Du et al 2018;Jiang and Xu 2019;Zhang et al 2019c) or three (Dou et al 2019) transition metals can be mixed to make one catalyst with high performance. Tables 3 and 4 summarize reported single and mixed transition metalbased catalysts, respectively.…”
Section: Transition Metal-based Catalystsmentioning
confidence: 99%
“…For example, two different single oxides (CeO2, Co3O4) were combined to study their synergistic effect on catalytic oxidation of toluene, and it was found that CeO2-CoOx exhibited outstanding catalytic activity compared to pure CeO2 and Co3O4 (Zhang et al 2019d). Dou et al (2019) used environmentally friendly bacterial cellulose to synthesize CuO-CeO2-ZrO2…”
Section: Mixed Transition Metal-based Catalysts For Toluene Oxidationmentioning
confidence: 99%